Borealization of nearshore fishes on an interior Arctic shelf over multiple decades. Issue 7 (4th January 2023) - von Biela, Vanessa R.; Laske, Sarah M.; Stanek, Ashley E.; Brown, Randy J.; Dunton, Kenneth H.
Abstract: Borealization is a type of community reorganization where Arctic specialists are replaced by species with more boreal distributions in response to climatic warming. The process of borealization is often exemplified by the northward range expansions and subsequent proliferation of boreal species on the Pacific and Atlantic inflow Arctic shelves (i.e., Bering/Chukchi and Barents seas, respectively). But the circumpolar nearshore distribution of Arctic‐boreal fishes that predates recent warming suggests borealization is possible beyond inflow shelves. To examine this question, we revisited two nearshore lagoons in the eastern Alaska Beaufort Sea (Kaktovik and Jago lagoons, Arctic National Wildlife Refuge, Alaska, USA), a High Arctic interior shelf. We compared summer fish species assemblage, catch rate, and size distribution among three periods that spanned a 30‐year record (baseline conditions, 1988–1991; moderate sea ice decline, 2003–2005; rapid sea ice decline, 2017–2019). Fish assemblages differed among periods in both lagoons, consistent with borealization. Among Arctic specialists, a clear decline in fourhorn sculpin ( Myoxocephalus quadricornis, Kanayuq in Iñupiaq) occurred in both lagoons with 86%–90% lower catch rates compared with the baseline period. Among the Arctic‐boreal species, a dramatic 18‐ to 19‐fold increase in saffron cod ( Eleginus gracilis, Uugaq) occurred in both lagoons. Fish size (length) distributions demonstrated increases in the proportion of larger fish for most species examined, consistent with increasing survival and addition of age‐classes. These field data illustrate borealization of an Arctic nearshore fish community during a period of rapid warming. Our results agree with predictions that Arctic‐boreal fishes (e.g., saffron cod) are well positioned to exploit the changing Arctic ecosystem. Another Arctic‐boreal species, Dolly Varden ( Salvelinus malma, Iqalukpik), appear to have already responded to warming by shifting from Arctic nearshore to shelf waters. More broadly, our findings suggest that areas of borealization could be widespread in the circumpolar nearshore. Abstract : Borealization is community reorganization where Arctic species are replaced by boreal species as climate warms. In marine settings, borealization research has focused on the inflow Arctic shelves as gateways between boreal and Arctic ecosystems. We show that borealization can also occur on interior Arctic shelves well beyond the gateways by focusing on two nearshore lagoons with unusually good data records spanning three decades of rapid sea ice decline. Our findings suggest borealization could be widespread across the circumpolar nearshore.